O GÊNERO RELATÓRIO DE ESTÁGIO NO ENSINO TÉCNICO INTEGRADO AO ENSINO MÉDIO - Santos, Graciela Beck de Bitencourt dos (2021)
This research is based in the Applied Linguistics, named “The internship report in the Technical Education Integrated to High School", sought to analyze the linguistic-discursive characteristics, as well to analyze the genre by the bias of systemic-functional linguistics, based on the linguistic theory of Hasan (1989). The referred genre was produced by the students of the Technical course in Agriculture Integrated with High School, at the Federal Institute Farroupilha Campus São Vicente do Sul, with the purpose to obtain the title of Technical in Agriculture at this Technical School. By a documentary qualitative research, the analysis was accomplished in ten produced reports approved in the year of 2019, that are archived in the Internship Sector of that institution. From this investigation, we recognize the Contextual Configuration, through the elucidation of the three variables of field, tenor and mode, as well as we analyzed the Generic Structure Potencial of the internship report produced in order to describe the activities performed during the mandatory curricular internship practice of the Technical Course in Agriculture Integrated with High School at the Federal Institute Farroupilha Campus São Vicente do Sul, through the presence and recurrence of the pretextual, textual and post-textual elements, appointed as obrigatory, optional or iterative elements.